Design and Implementation of the Mu'adalah Curriculum at Musthafawiyah Islamic Boarding School: Balancing Tradition and Innovation - Manshuruddin Manshuruddin; Mardianto Mardianto; Siti Halimah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the design and implementation of the Mu’adalah curriculum at Pesantren Musthafawiyah, examining how traditional Islamic educational values are integrated with modern pedagogical innovations to cultivate globally competent scholars. A qualitative case study approach was employed, utilizing observations, in-depth interviews, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, encompassing data reduction, display, and conclusion drawing. The Mu’adalah curriculum is rooted in mu’adalah salafiyah and emphasizes classical Islamic texts (kitab kuning). It integrates multiple design frameworks: subject-centered (focusing on religious instruction), learner-centered (addressing individual student needs), problem-centered (responding to contemporary educational challenges), and book-centered (anchored in traditional literature). Implementation occurs across intracurricular, extracurricular, and hidden curriculum activities, aiming to produce students with strong scholarly capability (ulama), moral excellence (akhlak karimah), and global readiness. Evaluation includes diagnostic, formative, and summative assessments aligned with educational objectives. Findings underscore the effectiveness of integrating Islamic tradition with modern methodologies in fostering students who are both spiritually grounded and competitive in global contexts. Nonetheless, challenges remain in achieving seamless interdisciplinary integration and adapting to evolving global educational standards. Pesantren Musthafawiyah exemplifies a successful model of Islamic education that balances tradition and innovation. Future efforts should focus on enhancing interdisciplinary approaches to further align student competencies with global demands.